2020
DOI: 10.2337/dc19-1459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Glucose Monitoring on Metrics of Glycemic Control in Diabetes: A Systematic Review With Meta-analysis of Randomized Controlled Trials

Abstract: BACKGROUNDContinuous glucose monitoring (CGM) provides important information to aid in achieving glycemic targets in people with diabetes. PURPOSEWe performed a meta-analysis of randomized controlled trials (RCTs) comparing CGM with usual care for parameters of glycemic control in both type 1 and type 2 diabetes. DATA SOURCESMany electronic databases were searched for articles published from inception until 30 June 2019. STUDY SELECTIONWe selected RCTs that assessed both changes in HbA 1c and time in target ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
147
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(170 citation statements)
references
References 46 publications
15
147
1
7
Order By: Relevance
“…Continuous glucose monitoring (CGM) overcomes the problems inherent in HbA1c and SMBG by informing conse-quent glucose level with various CGM metrics to better understand an individual's unique glycemic profiles, eventually leading to improved glycemic control. Moreover, since the sensor accuracy [7], convenience of use [8], and reimbursement has improved and numerous studies have shown improvement in glycemic control regardless of diabetes type and insulin delivery method [9], CGM use is rapidly expanding.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous glucose monitoring (CGM) overcomes the problems inherent in HbA1c and SMBG by informing conse-quent glucose level with various CGM metrics to better understand an individual's unique glycemic profiles, eventually leading to improved glycemic control. Moreover, since the sensor accuracy [7], convenience of use [8], and reimbursement has improved and numerous studies have shown improvement in glycemic control regardless of diabetes type and insulin delivery method [9], CGM use is rapidly expanding.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in effective diabetes self-management often requires a great attention to meals, regulating insulin doses, planning physical exercise or working activities and facing psychological stress [1]. The recent innovations in technologies aimed at diabetes management have largely enhanced the ability to improve glycemic control with glucose sensing, glucose-responsive insulin delivery systems and tools for data management which lessened the burden of self-care [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of continuous glucose monitoring (CGM) has transformed how type 1 diabetes is managed and enabled better monitoring of glucose during exercise [ 11 , 12 ]. The use of CGM systems has been shown to improve time-in-range, while reducing HbA1c levels and risk of hypoglycemia [ 13 , 14 , 15 , 16 ]. Additionally, it has led to the development of closed-loop systems associated with significant improvements in time-in-range [ 17 ].…”
Section: Introductionmentioning
confidence: 99%